Consciousness as a framework condition of cognition and methodologization - Furman, Anatoliy V. (Psyhology & society, 2019)
Actual problem of modern philosophical and psychological discourse is the desire to know the ontological nature of consciousness and thus understand its phenomenal pleroma (which means completeness, multiplicity) representation in everyday life of the human being, that becomes one of the most important tasks as a theoretical psychology, and in fact applied, primarily experimental. It is convincingly proved in the article that the mentioned problem can be solved only on the new philosophical-methodological grounds that think actively allow to achieve significantly different level-foreshortening of professional methodologization and simultaneously open still unexplored horizons of essential cognition as non-natural (the substantial, subjective, self-sufficient) reality. In the author’s experience of theorizing it means the creation of highly complex methodological optics which involves at least four lens modules into a single multi-function construction which makes it possible on the principles of complementarity to combine intellectual means of universal (vita-cultural methodology), general (research program of professional methodologization), special (cyclically-step approach) and single (methodology of paradigmal researches in psychology). In addition, starting to “declassify” the essential layers of consciousness, we must reckon with the five-segment organization of the world of modern psychology when a psychologist-researcher in one person every minute claiming the actual course of the flow of its life consciousness, appears as a theorist, and methodologist, and enlightener, and experienced practitioner, and the designer of its Self, self-individuality. Actualization of marked cycles or rhythms of vision, that is the discretion of the meaning in aforementioned positioning of psychologist, gives reason to conclude about the essence of existential matter of individual consciousness, namely about its ideal semantic horizon, which is formed as a local organization from the depths of the potential objectivity. That’s intentional acts of personal existence, thanks to the strenuous action of the thought-experiences, correlate situational eventfulness of awareness and meaning-certainty of the human life. At the same, modes of personal awareness, operating ideally filled material of intentionally localized objectivity in isolation from the objects of the material world, are causing partial or total identifying earlier worked out by him sense-schemes, meanings, values. Innovative forms of methodologization (seminars, sessions, orgactive games and other step-imitation organization) allow purposefully designing intensive group thought communication and thus actualize the unknown spaces of consciousness as the existential-being givens. We are talking primarily about a holistic architectonic of concepts which in the author’s reflection on the level of categorical concepts (“method”, “thinking”, “methodologization”, “methodological thinking”, “methodological activity”, “think activity”, “methodology”) is organized as a binary thought scheme in which to consciousness and self-consciousness there is a space of fifth – the transcendental – element; as a result, these categorical concepts represent the highest (transcendental, in fact spiritual) forms of the existential human presence in the world. Moreover, to the consciousness as “the most obvious non-obviousness” inherent paradox, problem-dialogical rhythm of situational continuous existence that is determined by that internal stress which outlined limit sense-forms of spectra of vector reasoning and natural diversity of signification and evaluation. That’s why consciousness is a framework condition as psychological knowledge, requiring perfect supernatural reflexivity and any other (philosophical, scientific, applied) methodologization which is impossible without specially created intellectual tools and instruments. The universal fact from the life of consciousness that has acquired the status of the law is the inevitability of name or naming from which the genetically primary forms of the manifestation of the conscious ability of a person to be - concepts, constructs, categories are begun, and from which appears existentially open, bifurcation duality of the intentional existence of this ability on the verge of modes of noumenal and phenomenal, external and internal, material and ideal. On this basis, the beyond-subjectivity and superculturalism of the sphere of consciousness is appeared, that self-eliminates through the ability of transcendence, fills the beyond-objective gap or corridor of the being as the state of an actually spontaneous, albeit missed, experience of conscious effort. It is argumented that in this sense consciousness is non-objective and beyond-objective nothing and simultaneously experienced and historically everything, and therefore the intentional, substantially tense, maximally hidden side of human existence, which essentially is not static, but dynamics, is not a structure, but a multifunctional, not dependence, but freedom, not a given, but an existential. In view of this, the exceptional relevance and heuristics of the development, along with the known achievements in the domain of meta theory, meta-methodology of consciousness, are noted.